Is small‐bowel capsule endoscopy effective for diagnosis of esophagogastric lesions related to portal hypertension?. Issue 3 (March 2014) - Aoyama, Taiki; Oka, Shiro; Aikata, Hiroshi; Nakano, Makoto; Watari, Ikue; Naeshiro, Noriaki; Yoshida, Shigeto; Tanaka, Shinji; Chayama, Kazuaki
Abstract Background and Aim Effectiveness of capsule endoscopy (CE) for screening the small bowel in patients with portal hypertension (PHT) has been reported. However, few reports discuss CE detection of specific esophagogastric lesions related to PHT. Thus, we assessed whether CE is useful for detecting such lesions. Methods One hundred nineteen consecutive patients with PHT comprised the study group. All had undergone esophagogastroduodenoscopy (EGD) prior to CE. The diagnostic yield of CE for esophageal varices (EVs), gastric varices (GVs), and portal hypertensive gastropathy (PHG) was evaluated. In addition, diagnostic yield in relation to form, location of the varices, grade, and extent of PHG was evaluated. Results EVs were found by EGD in 71 patients. The overall diagnostic yield of CE for EVs was 72% (51/71). The diagnostic yield was significantly greater for F2/F3 EVs than for F1 EVs (87% vs 61%, P = 0.03). The diagnostic yield was significantly greater for Lm/Ls EVs than for Li EVs (85% vs 55%, P = 0.01). The diagnostic yield was significantly greater for locus superior/locus medialis EVs than for locus inferior EVs (85% vs 55%, P = 0.01). GVs were found by EGD in 29 patients. Only one case was detected by CE. PHG was found by EGD in 35 patients. The diagnostic yield of CE for PHG was 69% (24/35). There was no difference in diagnostic yield between cases of severe and mild PHG (82% vs 63%, P = 0.44). Diagnostic yield of CE for PHG in the gastric body was significantly greater than that in the fundus (100% vs 48%, P = 0.0009). Conclusion CE is reliable for diagnosis of F2/F3 and/or Lm/Ls EVs and of PHG in the gastric body.